The Impact of Agile Leadership on Employee Performance with Job Satisfaction as a Mediating Variable - Pratama, Rifky Marda; Almansur, Fauzan (At-Tadbir : jurnal ilmiah manajemen, 2024)
This research aims to determine the effect of agile leadership on employee performance through job satisfaction at PT Jago Bahasa Inspira, a service company that provides English language learning services located in Kediri. This type of research is descriptive research with a quantitative approach using the path analysis method. Sampling was carried out using the random sampling method. The research results show that: agile leadership has a significant positive effect on job satisfaction, agile leadership has a significant positive effect on employee performance, and agile leadership has a significant positive effect on employee performance through job satisfaction Agile leadership and job satisfaction have a strong relationship, especially among young workers (Gen Z). Because there is a tendency to choose a workplace based on a non-toxic boss. Job satisfaction has a close relationship with employee performance, where high levels of job satisfaction tend to decrease positively with increasing individual performance. When employees feel satisfied with their work environment and working conditions, this can motivate them to contribute more to their tasks. Companies are advised to continue to maintain agile leadership while still paying attention to salary systems and promotions to continue to improve employee performance.